Enhancing productivity and livelihoods among smallholder irrigators through biochar and fertilizer amendments [Abstract only] - Jenkins, M.; Souvanhnachit, M.; Rattanavong, S.; Maokhamphiou, B.; Sotoukee, T.; Pavelic, Paul; Sarkis, M.; Downs, T. (2015)
Climate change and climate variability pose significant risks to smallholders in the rainfed lowlands of Lao PDR. Increased surface temperatures, declining rainfall, persistent drought and depletion of soil nutrients all serve to impact agricultural productivity and livelihoods. This study investigates the impact of five treatments on soil nutrients, moisture, plant growth, and yield of water spinach (Ipomoea aquatica). The treatments tested were rice husk biochar only, biochar inoculated with manure, manure tea, inorganic fertilizer and the control. The costs and benefits of the treatments were also assessed. The randomized complete block design was used to assign five treatments and eight replications to the experimental units. Biochar was produced through slow pyrolysis. Soil physical properties were assessed with the visual soil assessment method and 15-randomized soil samples were collected for chemical analyses. Sprinklers were used for irrigation and a weather station installed to monitor the climate. Descriptive statistics and analysis of variance were used to analyze the data. Costs-benefits evaluation of the treatments was conducted to determine the net benefits relative to the initial costs ratio. The analysis of variance of mean yield indicates that the difference in yield among the treatments was highly significant. The computed F value (8.08) was higher than the tabular F value (4.07) at the 1% level of significance. The calculated coefficient of variance of mean yield was 17.33%. The net benefits to initial costs ratio of treatments suggest that the control (5.84), biochar inoculated with manure plus NPK (0.93), and biochar plus manure (0.87) are preferred. The net benefits and initial costs evaluation of treatments is important to assess whether utilizing these treatments would impact smallholders’ livelihoods. The results of this study contribute to the evidence that biochar could play an essential role to mitigate climate change risks by enhancing soil quality and increase agricultural productivity.